Size-controlled InGaN/GaN nanorod LEDs with an ITO/graphene transparent layer - Shim, Jae-Phil; Seong, Won-Seok; Min, Jung-Hong; Kong, Duk-Jo; Seo, Dong-Ju; Kim, Hyung-jun; Lee, Dong-Seon (IOP PUBLISHING LTD, 2016)
We introduce ITO on graphene as a current-spreading layer for separated InGaN/GaN nanorod LEDs for the purpose of passivation-free and high light-extraction efficiency. Transferred graphene on InGaN/GaN nanorods effectively blocks the diffusion of ITO atoms to nanorods, facilitating the production of transparent ITO/graphene contact on parallel-nanorod LEDs, without filling the air gaps, like a bridge structure. The ITO/graphene layer sufficiently spreads current in a lateral direction, resulting in uniform and reliable light emission observed from the whole area of the top surface. Using KOH treatment, we reduce series resistance and reverse leakage current in nanorod LEDs by recovering the plasma-damaged region. We also control the size of the nanorods by varying the KOH treatment time and observe strain relaxation via blueshift in electroluminescence. As a result, bridge-structured LEDs with 8 min of KOH treatment show 15 times higher light-emitting efficiency than with 2 min of KOH treatment.
Keywords: LIGHT-EMITTING-DIODES; ETCH DAMAGE; GAN; ARRAYS; ENHANCEMENT